STRATEGI RENCANA PEMASARAN PERUMAHAN DALAM MENINGKATKAN PENJUALAN - Abdul Kamil, Imam; Alief Gilang, Muhamad; Pamungkas, Gilang; Abdillah, Ilham; Sundari, Asri (Jurnal Pelita Nusa, 2025)
This research aims to find problems, solve problems and develop new knowledge, by analyzing a case to find out a marketing plan that is suitable for marketing in "Cilame Permai" housing, the research method uses qualitative methods, because researchers can directly enter the object, carry out exploration questions, so that problems can be found clearly. Researchers in carrying out the qualitative research process can explore an object, the aim of this research is to find out suitable strategies for marketing houses in Cilame Permai (PT. Suburland). The marketing strategy used by PT. Suburland is to pay attention to housing marketing strategy indicators such as sales volume, sales growth rate, closing rate, return on investment, market share, customer satisfaction, awareness and brand recognition as well as marketing strategy dimensions, namely market segmentation, targeting, positioning, marketing mix, digital marketing, direct sales strategy, public relations strategy and product and service innovation, with this pattern PT. Subur Abadi Putra can find out the advantages and disadvantages as well as the opportunities that exist in the Cilame Permai housing complex.